The Impact of Mobile Number Portability on Firms Profitability in the United States - Shee, Anita (2013)
This dissertation examines the impact of mobile number portability on firms’ profitability in the United States. The event study methodology is employed to determine the effect of seven events related to mobile number portability on stock market performances. Specifically, the modified market and capital asset pricing models are used to facilitate this study. Furthermore, extended analyses controlling for leveraging is conducted. The results indicate that certain events cause some stocks to experience statistically significant positive cumulative abnormal returns while others experience statistically significant negative abnormal returns. Event 2 consistently leads to statistically significant estimates of cumulative abnormal returns for Nextel and United States Cellular Corporation in all model specifications. Several plausible explanations for these mixed results are discussed.